Isolation, Characterization, and Genomic Analysis of Three Novel E. coli Bacteriophages That Effectively Infect E. coli O18 - Fatma Abdelrahman; Nouran Rezk; Mohamed S. Fayez; Mohamed Abdelmoteleb; Reham Atteya; Mohamed Elhadidy; Ayman El-Shibiny (Microorganisms, 2022)
Escherichia coli (E. coli) is one of the most common pathogenic bacteria worldwide. Avian pathogenic E. coli (APEC) causes severe systemic disease in poultry (Colibacillosis), and accordingly, has an extreme risk to the poultry industry and public health worldwide. Due to the increased rate of multi-drug resistance among these bacteria, it is necessary to find an alternative therapy to antibiotics to treat such infections. Bacteriophages are considered one of the best solutions. This study aimed to isolate, characterize, and evaluate the potential use of isolated bacteriophages to control E. coli infections in poultry. Three novel phages against E. coli O18 were isolated from sewage water and characterized in vitro. The genome size of the three phages was estimated to be 44,776 bp, and the electron microscopic analysis showed that they belonged to the Siphoviridae family, in the order Caudovirales. Phages showed good tolerance to a broad range of pH and temperature. The complete genomes of three phages were sequenced and deposited into the GenBank database. The closely related published genomes of Escherichia phages were identified using BLASTn alignment and phylogenetic trees. The prediction of the open reading frames (ORFs) identified protein-coding genes that are responsible for functions that have been assigned such as cell lysis proteins, DNA packaging proteins, structural proteins, and DNA replication/transcription/repair proteins.